Survey of the publics' preferences for communication of medical radiation risk* Funding provided from Health Education England as part of the Higher Specialist Scientist Training programme. (1st June 2022) - Davies, Elizabeth; Peet, Deborah; Taylor, Michael J; Chung, Emma M L
Abstract: To comply with the Ionising Radiations (Medical Exposures) Regulations 2017, patients need to be adequately informed of medical radiation risks prior to exposure. This study used a survey developed in partnership with patients and members of the public to explore patient preferences for radiation risk communication. It was distributed through social media between 28/4/2020 and 18/7/2020. All respondents ( N = 376) wanted to be informed about radiation risk, though the threshold at which they wished to be informed varied. The current practice of displaying posters in waiting areas does not meet the expressed preference of the patients if used in isolation. Only 6% of respondents were satisfied with the commonly used statement that the 'risk is low' if used in isolation. The majority of respondents (73%) said they would not be concerned about an increase in the risk of cancer of less than 1 in 10 000. The level of risk at which patients express a concern and the methodology for risk communication has been evaluated and based on these findings, and pre-existing literature, a graded approach to radiation risk communication based on modality is proposed. Patients must be involved throughout the evolution of this practice.